Implementasi Pembelajaran Berbasis Proyek terhadap Hasil Belajar Siswa pada Pembelajaran Mesin Bubut - Pratama, Yuhanda Dicky; Indrawan, Eko; Refelino, Refelino; Abadi, Zainal (MASALIQ, 2024)
This study aims to analyze the project-based learning model on learning outcomes in class XI lathe subjects majoring in Mechanical Engineering SMK Negeri 1 Tanjung Raya. The type of research that the authors conducted was Quasi Experimental Design (pseudo / quasi experiment) research. The experimental research design used in this study was in the form of nonequivalent control group desaign. This study uses pre-test and post-test tests to students to see students' understanding before and after using the learning model, whether there is a good enough improvement after applying the learning model. Based on the results of research and discussion, Quasi-Experiment research in the subject of Lathe Machining Engineering class XI Machining Engineering SMK Negeri 1 Tanjung Raya can be concluded as follows. First, the project-based learning model in the experimental class in the Lathe Machining Engineering subject was successfully implemented in class XI of the Machining Engineering of SMK Negeri 1 Tanjung Raya. Second, student learning outcomes The acquisition of this final score increased from the previous average score of 53. Third, the skills and creativity of students in the subject of Lathe Machining Engineering Class XI Machining Engineering SMK Negeri 1 Tanjung Raya, carried out using a psychomotor assessment rubric and obtained an average score in the control class of 74 and the experimental class of 80.